Analysis of the Independent Curriculum Policy through the Implementation of the Project for Strengthening the Profile of Pancasila Students - kurniawan, jimi; Maisyaroh, Maisyaroh; Supriyanto, Achmad (Jurnal Akuntabilitas Manajemen Pendidikan, 2024)
The Merdeka Curriculum Policy in Indonesia aims to develop students' characters through the concept of the Pancasila student profile. One implementation of this policy is the Pancasila Student Profile Strengthening Project (P5), which is carried out in various schools, including SMK Negeri 1 Kepanjen. This study aims to analyze the implementation of P5 at SMK Negeri 1 Kepanjen as an effort to strengthen the students' characters. The research method used is descriptive qualitative with data collection techniques such as interviews, observations, and documentation. P5 activities at SMK Negeri 1 Kepanjen include art performances, work harvesting, and innovation exhibitions as part of the project implementation. P5 at SMK Negeri 1 Kepanjen aims to strengthen students' characters with a focus on Pancasila values, such as faith, devotion to God Almighty, global cooperation, independence, and critical and creative thinking. However, detailed policies regarding P5 in Indonesia are not available in the provided search results. Based on field observations, the project aims to (1) enhance students' understanding of Pancasila values at SMK Negeri 1 Kepanjen, (2) integrate Pancasila values into every aspect of students' lives in school and society, and (3) develop students' characters reflecting national spirit, tolerance, and social concern.